Development of KAREBU (cultural diversity card game) to enhance curiosity in fourth-grade elementary students - Mahanani, Etyka Rina; Ahdhianto, Erif; Barus, Yohannes Kurniawan (CV Rezki Media, 2025)
Background: Learning media is one of the important components of education. Objectives: The purpose of this research and development was to develop the KAREBU (Cultural Diversity Card) learning media to strengthen the curiosity character of fourth-grade students in the subject of Natural and Social Sciences with local cultural diversity material that is valid, practical, and effective. Methods: Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study developed KAREBU cards integrated with augmented reality (AR) technology. This research instrument is in the form of interviews, observations, and questionnaires given to instrument experts, material experts, media experts, and users, including teachers and students. Data collection stages were carried out through observation, interviews, needs questionnaires, validation questionnaires, practicality questionnaires, and curiosity questionnaires before and after using the media. Results: The results showed that the KAREBU learning media met the valid, practical, and effective criteria. KAREBU media received a validity score from material experts of 3.72 with a valid category, a score from media experts of 4.91 with a very valid category, and a score from users of 4.73 with a very valid category. The KAREBU learning media received a practicality score from teachers of 4.49 with a convenient category and a practicality score from students of 98.5% with a convenient category. The level of media effectiveness in strengthening students' curiosity was obtained from the results of the questionnaire before and after using the media, which was calculated using the N-Gain Score test with a value of 0.76 and high effectiveness criteria. Conclusions: Therefore, it was concluded that the KAREBU learning media effectively strengthens students' curiosity. Further studies could explore the long-term impacts of KAREBU on cross-cultural empathy.